Projections of esophageal cancer incidence trend in Jiangsu Province, China: a Bayesian modeling study - Weigang Miao; Yuanyuan Feng; Bijia Jiang; Yanan Wan; Xikang Fan; Renqiang Han; Jinyi Zhou (Journal of the National Cancer Center)
Objective: Esophageal cancer has made a great contribution to the cancer burden in Jiangsu Province, East China. This study was aimed at reporting esophageal cancer incidence trend in 2009–2019 and its prediction to 2030. Methods: The burden of esophageal cancer in Jiangsu in 2019 was estimated using 54 cancer registries’ data selected from Jiangsu Cancer Registry. Incident cases of 16 cancer registries were applied for the temporal trend from 2009 to 2019. The burden of esophageal cancer by 2030 was projected using the Bayesian age-period-cohort (BAPC) model. Results: About 24,886 new cases of esophageal cancer (17,233 males and 7,653 females) occurred in Jiangsu in 2019. Rural regions of Jiangsu had the highest incidence rate. The age-standardized incidence rate (ASIR, per 100,000 population) of esophageal cancer in Jiangsu decreased from 27.72 per 100,000 in 2009 to 14.18 per 100,000 in 2019. The BAPC model showed that the ASIR would decline from 13.01 per 100,000 in 2020 to 4.88 per 100,000 in 2030. Conclusions: According to the data, esophageal cancer incidence rates were predicted to decline until 2030, yet the disease burden is still significant in Jiangsu. The existing approaches to prevention and control are effective and need to be maintained.